ROLE OF PKK MOTHERS IN PROMOTING WOMEN'S REPRODUCTIVE HEALTH THROUGH BUTTERFLY PEA FLOWER TEA UTILIZATION - Arisda Candra Satriawati; Dian Permatasari; Laylatul Hasanah (Jurnal Smart Kebidanan, 2026)
Women’s reproductive health remains an important issue that requires promotive and preventive efforts at the community level. One of the local herbal plants increasingly used for health purposes is butterfly pea flower (Clitoria ternatea), which is known to contain antioxidants beneficial for maintaining body health. This study aimed to describe the role of PKK mothers in the utilization of butterfly pea flower tea for maintaining women’s reproductive health. The study used a descriptive quantitative design and was conducted among PKK mothers in Bangkalan, East Java. The population consisted of all PKK mothers in the study area, and 26 respondents were selected using a total sampling technique. Data were collected using structured questionnaires covering respondent characteristics, level of knowledge, and the role of PKK mothers in reproductive health education. The data were analyzed descriptively using frequency distributions and percentages. The results showed that most respondents had good knowledge regarding the benefits of butterfly pea flower tea and women’s reproductive health (76.9%). Most respondents also demonstrated good roles in promoting reproductive health through health education and community activities (65.4%). The study concludes that PKK mothers have an important role in promoting reproductive health awareness through the utilization of local herbal plants, particularly butterfly pea flower tea, within the community.